Role of L1CAM in retinoblastoma tumorigenesis: identification of novel therapeutic targets. Issue 4 (18th July 2021) - Dräger, Oliver; Metz, Klaus; Busch, Maike; Dünker, Nicole
Abstract : The study presented focuses on the role of the neuronal cell adhesion molecule L1 cell adhesion molecule (L1CAM) in retinoblastoma (RB), the most common malignant intraocular childhood tumor. L1CAM is differentially expressed in a variety of human cancers and has been suggested as a promising therapeutic target. We likewise observed differential expression patterns for L1CAM in RB cell lines and patient samples. The two proteases involved in ectodomain shedding of L1CAM (L1CAM sheddases: ADAM10 and ADAM17) were likewise differentially expressed in the RB cell lines investigated, and an involvement in L1CAM processing in RB cells could be verified. We also identified ezrin, galectin‐3, and fibroblast growth factor basic as L1CAM signaling target genes in RB cells. Lentiviral L1CAM knockdown induced apoptosis and reduced cell viability, proliferation, growth, and colony formation capacity of RB cells, whereas L1CAM‐ overexpressing RB cells displayed the opposite effects. Chicken chorioallantoic membrane assays revealed that L1CAM depletion decreases the tumorigenic and migration potential of RB cells in vivo . Moreover, L1CAM depletion decreased viability and tumor growth of etoposide‐resistant RB cell lines upon etoposide treatment in vitro and in vivo . Thus, L1CAM and its processing sheddases are potential novel targets for future therapeutic RB approaches. Abstract : We investigated the role of the neuronal L1 cell adhesion molecule (L1CAM) in retinoblastoma (RB), a malignant intraocular childhood tumor. L1CAM depletion induced apoptosis and reduced RB cell viability in vitro and tumor growth and migration in vivo . Thus, L1CAM together with its processing sheddases (ADAM10 and ADAM17) and identified downstream targets (ezrin, β‐galactoside‐binding protein galectin‐3, and fibroblast growth factor basic) are promising targets for novel therapeutic approaches.